Leukemia/lymphoma‐related factor (LRF) exhibits stage‐ and context‐dependent transcriptional controls in the oligodendrocyte lineage and modulates remyelination. Issue 12 (30th May 2017) - Davidson, Nathan L.; Yu, Fengshan; Kijpaisalratana, Naruchorn; Le, Tuan Q.; Beer, Laurel A.; Radomski, Kryslaine L.; Armstrong, Regina C.
ABSTRACT: Leukemia/lymphoma‐related factor (LRF), a zinc‐finger transcription factor encoded by Zbtb7a, is a protooncogene that regulates differentiation in diverse cell lineages, and in the CNS, its function is relatively unexplored. This study is the first to examine the role of LRF in CNS pathology. We first examined LRF expression in a murine viral model of spinal cord demyelination with clinically relevant lesion characteristics. LRF was rarely expressed in oligodendrocyte progenitors (OP) yet, was detected in nuclei of the majority of oligodendrocytes in healthy adult CNS and during remyelination. Plp/CreER T :Zbtb7a fl/fl mice were then used with cuprizone demyelination to determine the effect of LRF knockdown on oligodendrocyte repopulation and remyelination. Cuprizone was given for 6 weeks to demyelinate the corpus callosum. Tamoxifen was administered at 4, 5, or 6 weeks after the start of cuprizone. Tamoxifen‐induced knockdown of LRF impaired remyelination during 3 or 6‐week recovery periods after cuprizone. LRF knockdown earlier within the oligodendrocyte lineage using NG2CreER T :Zbtb7a fl/fl mice reduced myelination after 6 weeks of cuprizone. LRF knockdown from either the Plp/CreER T line or the NG2CreER T line did not significantly change OP or oligodendrocyte populations. In vitro promoter assays demonstrated the potential for LRF to regulate transcription of myelin‐related genes and the notch target Hes5, which has been implicated in control of myelin formation and repair. In summary, in the oligodendrocyte lineage, LRF is expressed mainly in oligodendrocytes but is not required for oligodendrocyte repopulation of demyelinated lesions. Furthermore, LRF can modulate the extent of remyelination, potentially by contributing to interactions regulating transcription. Abstract : Our studies provide the first evidence for stage‐dependent expression of LRF in the oligodendrocyte lineage during remyelination, and the potential for LRF to modulate the complex transcriptional control mechanisms that contribute to efficient and maintained remyelination.